Literature Review on High Definition Image Error Concealment - Ahamed Z, Ghouse; Jain, Anuj (International Journal of Engineering and Technology, 2018)
This paper is give us a overview of Error control method used in image or video transmission. Data in transmission is lost due to link failure or due to congestion and loss in packets, so the aim of this method is to protect data from these errors. Error detection coding and Error correction coding are two types of error control mechanism. Some of the error control mechanisms are Retransmission, Forward error correction, error concealment and error resilience. We are discussing a summary of three methods and Error Concealment in details.Â Â
Keywords: Retransmission; Error Concealment; Error Resilience; Forward Error Correction (FEC).